Investigating the interactions between populations five star hotels in Turkey - ATAMAN BERK, GÖKSEL (My University, 2015)
In this study, it was to illustrate how the interactions between populations may affect the founding rates of the organizations in these populations. Five-star hotels are seen either having a chain affiliation or as independent hotels. We examined the population of chain hotels and the population of independent hotels to observe the interactions between populations. We computed the densities of the two populations, the number of entries and exits into or out of the populations, room capacities and geographic locations of the hotels. Therefore, we demonstrate the differences between the two populations in terms of densities, size and location. When the density of chain hotels increases above average, the density of independent hotels decreases. Otherwise, when the density of independent hotels increases above average, the density of chain hotels is not affected. On these bases of hotel populations between 1976 and 2014, we formulated exploratory hypotheses to be tested on how the interaction between the two populations may affect their founding rates.
Keywords: Population Dynamics; Organizational Ecology; Organizational Density; Organizational Founding